Teknik Relaksasi dengan Alat Musik Tradisional Mandar Menurunkan Skala Nyeri pada Ibu Bersalin Kala I Fase Aktif - G, Sattriani; Mahmud, Abbas (Jurnal Kebidanan Malakbi, 2020)
The direct causes of maternal mortality rate are bleeding, eclampsia, abortion, infection, and prolonged labor. Maternal mortality rate can be minimized by safe, clean help, and prevent complications. Labor is a process that begins with uterine contractions causing progressive dilation of the cervix, birth of a baby, and labor of placenta and it is a natural process. This study aims to see the effectiveness of instrumental music relaxation techniques using traditional musical instruments on the labor process of inpartu mothers when phase I was active at Community Health Center in Tampa Padang, Mamuju. This study is an experimental study with a pre-experimental conception and use one group pretest-posttest conception with the population of maternal mothers at Tampa Padang Community Health Centre. The samples are pregnant women who entered the delivery room with inpartu diagnosis of the first stage/phase is active or the opening stage. The sampling technique was consecutive sampling which could be done by 31 people. The data then being analyzed with univariable analysis and bivariable analysis using the Wilcoxon Test with a significance level of 0.05 to see the interface relationship with the decrease in pain scale. The results showed a relationship in reducing pain scale of mothers who were given musical intervention with Mandar traditional musical instruments where p = 0.000. The conclusion of this study shows that by applying instrumental music relaxation techniques with traditional Mandar musical instruments, mothers can adjust to pain during labor so that it can reduce the pain scale in mothers in labor when phase 1 is active.